ECOFOLKLORE AND INDIGENOUS WISDOM IN EASTERINE KIRE’S NOVELS - Mero, Wedeu; Thokchom Sunanda Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intersection of ecofolklore and indigenous wisdom in the novels of Easterine Kire, a prominent Naga writer from Northeast India. Through a comprehensive analysis of Kire’s works, particularly A Naga Village Remembered (2003), Son of the Thundercloud (2016), and When the River Sleeps (2014), this study examines how the author incorporates traditional Naga folklore, environmental consciousness, and indigenous knowledge systems into her narratives. The research employs a mixed-method approach, combining textual analysis with ecocritical and postcolonial theoretical frameworks. The findings reveal that Kire’s novels serve as a repository of Naga ecofolklore and indigenous wisdom, highlighting the intricate relationship between the Naga people and their natural environment. Furthermore, the study demonstrates how Kire’s writing contributes to the preservation and dissemination of traditional ecological knowledge while addressing contemporary environmental and cultural challenges.